PHARMACOKINETIC VARIABILITY AND THERAPEUTIC DRUG MONITORING OF SYSTEMIC ANTIFUNGAL AGENTS: MITIGATING HEPATOTOXICITY AND OPTIMIZING EFFICACY IN CRITICALLY ILL COHORTS (World Bulletin of Public Health, 2026)
The pathophysiological complexity of invasive fungal infections in immunocompromised and critically ill patients dictates a highly individualized pharmacological approach, driven by unpredictable drug distribution and extreme metabolic variances. This study evaluates the precise clinical efficacy and toxicity profiles of utilizing broad-spectrum systemic antifungal agents—specifically triazoles and echinocandins—by comparing conventional weight-based dosing against proactive Therapeutic Drug Monitoring (TDM) protocols. A prospective clinical analysis was conducted involving 124 adult patients diagnosed with invasive candidiasis or presumed invasive pulmonary aspergillosis. Subjects were stratified into a conventional empirical dosing cohort (n=60) and a targeted pharmacokinetic-guided cohort (n=64) utilizing high-performance liquid chromatography to measure precise trough concentrations of voriconazole and fluconazole. Clinical data indicate that unadjusted, static dosing regimens frequently result in dangerous pharmacokinetic extremes due to non-linear hepatic metabolism and saturable elimination pathways. The targeted TDM cohort demonstrated an 85.9% rate of achieving early target therapeutic serum concentrations (trough levels between 1.5 and 5.5 mcg/mL for voriconazole), directly correlating with a rapid decline in serum galactomannan antigen indices and complete mycological eradication. Conversely, the empirical dosing group exhibited a 21.6% incidence of severe, therapy-limiting hepatotoxicity driven by unrecognized supratherapeutic accumulation, alongside a 15.0% clinical failure rate due to subtherapeutic tissue penetration. The dynamics of the observed results suggest that the inherent physiological volatility of critically ill patients renders traditional standardized antifungal posology unsafe. Comprehensive pharmacotherapy must actively integrate continuous serum concentration monitoring and real-time hepatic enzyme evaluation to guarantee fungicidal penetrance while actively neutralizing the threat of catastrophic organ damage.